Confirming the Effects of Qinghuayin against Chronic Atrophic Gastritis and a Preliminary Observation of the Involved Inflammatory Signaling Pathways: An In Vivo Study. (26th September 2018) - Li, Sihan; Huang, Minghan; Chen, Qin; Li, Shunan; Wang, Xin; Lin, Jianlong; Zhong, Guodong; Lin, Ping; Asakawa, Tetsuya
Abstract : Background. Qinghuayin (QHY) is a Chinese formula that is widely used in the treatment of chronic atrophic gastritis (CAG). This study was planned with the following objectives: ( 1 ) confirming the efficacy of QHY in a rat model of CAG and ( 2 ) performing a preliminary observation of the changes in several inflammatory signaling pathways potentially involved in the QHY mechanisms. Methods. A total of 33 rats were used in this study; they were divided into the control (n = 12) and model (n = 21) groups. QHY was administrated to both the groups. We assessed the pathological manifestations and the serum tumor necrosis factor alpha (TNF- α ) level as markers of efficacy. We also performed a preliminary observation of the changes in the protein and messenger ribonucleic acid (mRNA) expression of toll-like receptors 4 (TLR4), MyD88, NF- κ B, and COX-2. Results. The pathological changes induced in the rats by the establishment of the CAG models were recovered by low and high doses of QHY. Their serum TNF- α level also reduced following low- and high-dose QHY treatment. Protein and mRNA expressions of TLR4, MyD88, NF- κ B, and COX-2 were upregulated by the establishment of CAG models and downregulated by the administration of low- and high-dose QHY. Conclusions . Our data confirm the efficacy of QHY as an adjuvant therapy, based on the theories in traditional Chinese medicine. The preliminary observations indicate that the downregulation of the enhanced inflammatory signaling pathways might be crucial QHY mechanisms that need further verification.